Concordância interobservador na avaliação ultrassonográfica das mamas de casos classificados como categoria 0 á mamografia - Maurilio da Cruz Trigueiro (2012)
The study was carried out to evaluate the interobserver agreement of ultrasonography (US) in cases classified as BI-RADS TM category "0" mammogram. The US method was applied in 60 cases classified as category "0" at mammography in the period 2010 to 2011. Mammograms and ultrasound examinations of these patients were classified according to the fourth edition of BI-RADSTM. We performed the agreement on the categories and their sonographic descriptors among three observers. In cases of disagreement as to the categorization was reevaluated for consensus. Most cases showed images considered negative, benign and probably benign totaling 88.4% of cases. The results showed that the interobserver agreement in the categorization of breast ultrasound was excellent (Kappa = 0.83), with variation between categories (Category "1": Kappa = 1.00; Category "2": Kappa = 0.97; Category "3": Kappa = 0.64 and Category "4": Kappa = 0.46). The agreement on the descriptors for margin was lower limits of the lesion and echo pattern for both final categorization as for the categories "3" and "4". In 11 cases (18.3%) sonographic classification was discordant. After the revaluation for consensus, cases diagnosed as category "4" decreased in 28.5%. The indication for invasive workup could potentially be avoided in cases initially diagnosed as a category "4" due to the revaluation of discordant results between the three examiners.